Food waste: Challenges and opportunities in sustainable operations - Luciana Marques Vieira (Fundação Getulio Vargas, 2021)
The call for papers for this Special Forum resulted in a very competitive selection of 37 being submitted. After several rounds of blind review, six papers were selected for this Special Forum. They clearly illustrate the challenges of carrying out research into sustainable operations and food waste reduction. They examine a variety of units of analysis and theories, which are embedded in different geographical contexts, and use a variety of analytical methods. What they all have in common is that they reveal just how applicable research aimed at finding solutions for reducing food waste is. In this Introductory article, we summarize the contributions of each of these six papers to the literature.